Graphic design - Hannam, Ben (--For dummies., 2025)
The complete, full-color graphic design guide for beginners The field of graphic design is constantly evolving, with new design tools, methods, technology, and modes of expression being introduced all the time. Graphic Design For Dummies will teach you how to get started, introducing you to basic design principles as well as the latest best practices, software, and trends. You'll learn how to successfully plan and execute compelling design projects, even if you're not a trained designer. This fun and friendly book will empower you with the information you need to create design solutions. You'll also have the opportunity to test your skills with a series of interactive design activities, starting with step-by-step guidance and slowly building up your skills until you're ready to fly solo. Unleash your inner graphic designer with this Dummies guide. Create compelling visuals for a wide range of tasks and purposes Learn the basic concepts of graphic design and get the tools you need to start Get hands-on experience by following tutorials to create great designs Become proficient in graphic design--no art degree needed Graphic Design For Dummies is a practical and user-friendly resource for those looking to create better design solutions quickly.